1989
DOI: 10.1111/j.1365-2311.1989.tb00961.x
|View full text |Cite
|
Sign up to set email alerts
|

Onset and spread of an African army worm upsurge

Abstract: Abstract. 1. Onset and spread of the severe outbreaks of African armyworm, Spodoptera exempta (Walk.), over Ethiopa, Kenya, Tanzania and Burundi in late 1984 have been analysed in relation to trap and weather records.2. Although first outbreaks in each country appeared progressively further south, winds on the best estimated dates of moth concentration and egg laying blew from directions precluding moth movements between them.3. Such independently developing outbreaks are called ‘primary’ to distinguish them … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0

Year Published

1992
1992
1998
1998

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 20 publications
0
20
0
Order By: Relevance
“…African armyworm outbreaks were mapped by location and reporting date and the distribution of outbreaks was then summarised, by degree square and by week of estimated moth arrival, prior to oviposition. Dates of moth arrival were estimated using development tables and a regression described by Pedgley et al (1989). The association between outbreaks and rainstorms was then tested, by comparing the frequency with which outbreaks and rainstorms occurred in the same degree square and week with the frequency of each occurring alone, and of neither occurring, using the chi-square statistic.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…African armyworm outbreaks were mapped by location and reporting date and the distribution of outbreaks was then summarised, by degree square and by week of estimated moth arrival, prior to oviposition. Dates of moth arrival were estimated using development tables and a regression described by Pedgley et al (1989). The association between outbreaks and rainstorms was then tested, by comparing the frequency with which outbreaks and rainstorms occurred in the same degree square and week with the frequency of each occurring alone, and of neither occurring, using the chi-square statistic.…”
Section: Methodsmentioning
confidence: 99%
“…A significant association has also been found in eastern Africa between the timing of oviposition leading to outbreaks early in the armyworm season (October-March) and rainstorms, especially those that followed dry periods (Tucker and Pedgley 1983;Pedgley et al 1989). Analyses of seasonal rainfall found that severe armyworm seasons often followed poor early rains (especially those in November) (Harvey and Mallya 1995;Tucker 1984).…”
mentioning
confidence: 94%
“…The relationship between the time and place of moth catches, topography, rainfall and subsequent outbreaks was directly observed during a mark-and-capture experiment in 1982 (Rose et al 1985) and during the major armyworm upsurge in 1984 (Pedgley et al 1989). Observations were consistent with peak oviposition at times and places of high rainfall and of high male moth catches in pheromone traps in the lee of hills.…”
Section: Moth Immigrationmentioning
confidence: 99%
“…Many caterpillars march together in one direction but the direction is not consistent at any one place. Although feeding has been observed at night, feeding occurs mainly during the day and food plants growing in (Brown 1962;Rose 1975) and inferred (Blair et al 1980;Pedgley et al 1989) for outbreak generations over wide regions of the higher parts of east Africa.…”
Section: Field Infestationsmentioning
confidence: 99%
See 1 more Smart Citation